Pengaruh Tingkat Pendidikan, Pengangguran dan Pertumbuhan Ekonomi Terhadap Kemiskinan di Provinsi Bali - Aristina, Ita; Budhi, Made Kembar Sri; Wirathi, I G.A.P.; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
Poverty is a big problem in the province of Bali. The problem of poverty can not be accomplished in a short time in because poverty is a multisectoral problem that involves many sectors of society, ranging from health, education and labor. This study aims to determine the effect of simultaneous and partial levels of education, unemployment, economic growth on poverty. The data used in this research is secondary data. The data collection is done by non-participant observation. Data processed by multiple linear regression analysis. The test results with the results obtained Eviews 6 Level of Education, Unemployment and Economic Growth simultaneous and significant influence on Poverty in the province of Bali. In partial, Education Level and Economic Growth significant negative effect on Poverty in the province of Bali, while the unemployment variable positive and significant effect on Poverty in the province of Bali.
Keywords: tingkat pendidikan; pengangguran; pertumbuhan ekonomi; kemiskinan